Investigación de hongos filamentosos superiores hialino en pacientes del asilo de bien público de la junta de beneficencia de guayaquil, durante el período de enero a junio del 2015. - Silva Morocho, Frank Andrés (2015)
This research aims to determine the incidence of filamentous fungi higher, with the main representatives dermatophytes which are the causative agents of ringworm, study conducted in patients asylum "the public good" of the Board Guayaquil Welfare, knowing that their physiological condition are likely to get fungal diseases. The development of the thesis for better understanding is divided into four sections. Chapter I contains the statement of the problem, the problem formulation, objectives and justification, which is the reason for this research. Chapter II consists of the theoretical framework, it is composed of subjects as main characteristics of fungi, their classification in relation to clinical interest, the description of genera and more important in the medical field and the diseases they cause species.